Making strange: Race science and ethnopsychiatric discourse - Manganyi, Chabani (My University, 1984)
Discourse about Europe's Others, about "primitive races", about "Orientals", about Jews, Africans and so-called Negroes is omni present even in such momentous intellectual undertakings as psychoanalysis and Marxism. What one encounters are a series of significant tendencies all amounting to the verbal device through which something familiar is made to appear strange - 'making strange' as Volosinov would put it.
African Studies Seminar series. Paper presented October 1984
Keywords: Social psychology; Race awareness. South Africa. Psychological aspects.; Ethnopsychology. South Africa; Psychotherapy. South Africa. Cross-cultural studies